1993
DOI: 10.1056/nejm199311183292102
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Administration of Respiratory Syncytial Virus Immune Globulin to High-Risk Infants and Young Children

Abstract: Administration of high doses of respiratory syncytial virus immune globulin is a safe and effective means of preventing lower respiratory tract infection in infants and young children at high risk for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
398
2
5

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 694 publications
(415 citation statements)
references
References 39 publications
10
398
2
5
Order By: Relevance
“…Previous studies have suggested that ' high risk ' infants are the most important target group for intervention strategies [13][14][15]. Our data suggest that the majority (98 %) of children under 1 year of age hospitalized with reported RSV infection are not ' high risk ' (i.e.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have suggested that ' high risk ' infants are the most important target group for intervention strategies [13][14][15]. Our data suggest that the majority (98 %) of children under 1 year of age hospitalized with reported RSV infection are not ' high risk ' (i.e.…”
Section: Discussionmentioning
confidence: 60%
“…The relative sparing of infants from virus-associated lower respiratory tract disease in the first weeks or months of life correlates with the level of passively acquired maternal Abs to RSV (7), parainfluenza virus type 3 (PIV3) (8), or influenza viruses (9). Administration of pooled human IgG containing a high titer of RSV neutralizing Abs or of a humanized murine RSV-specific mAb prevents severe RSV disease in high-risk infants and children (10,11). Passive transfer of RSV polyclonal immune sera or neutralizing RSV mAbs protects the lower, and to a lesser extent, the upper respiratory tract of rodents against replication of RSV challenge virus (12)(13)(14)(15).…”
Section: R Espiratory Syncytial Virus (Rsv)mentioning
confidence: 99%
“…Les IVIG, purifiées et conditionnées industriellement par une dizaine de compagnies internationales, sont des préparations monomériques standardisées (98 % d'IgG, incluant des IgG1, IgG2 et IgG3 dans les proportions normales du sérum [8]), dûment contrôlées pour l'absence d'agents pathogènes et dont l'efficacité a été démontrée dans de nombreuses études cliniques [9][10][11][12][13][14][15] récapitulées dans le Tableau I. Leur efficacité contre un large éventail d'infections est attribuée au fait qu'elles comportent une grande diversité d'anticorps contenus dans les plasmas des donneurs naturellement immunisés ou vaccinés contre une grande diversité de pathogènes primaires ou opportunistes [8]. Cependant, les effets observés dans certains essais cliniques sont parfois discordants [10,11] (Tableau I), car les IVIG sont des mélanges d'IgG provenant des plasmas de milliers de donneurs et leur composition peut varier d'un fabricant à l'autre et de lot à lot [8].…”
Section: Immunothérapie Passive Des Infections Respiratoires Par Immuunclassified
“…Cela est probablement dû au fait que la quantité nécessaire et suffisante d'anticorps neutralisants est délivrée au site même de développement du processus infectieux [5, 16-18, 23, 24]. La neutralisation précoce de l'infection respiratoire est obtenue par des fragments F(ab')2 avec la même efficacité que les IgG complètes, suggérant que l'effet protecteur, indé-pendant de Fc, ne requiert ni la fixation du complément ni l'intervention des phagocytes, et offre donc la possibilité de traiter des patients leucopéniques ou déficitaires en complément [4,5,[9][10][11][12]. Cependant, l'efficacité d'une telle approche thérapeutique dans des conditions inflammatoires chez l'homme, comme l'asthme ou la mucoviscidose, n'a pas été évaluée.…”
Section: Immunothérapie Des Infections Respiratoires Par Administratiunclassified